Czech Republic : Selected Issues. (IMF Staff Country Reports; Country Report, 2019)
This Selected Issues paper investigates the direct and indirect exposure of the Czech Republic to these external risks. The Czech Republic is a small open economy that has become increasingly reliant on export-driven growth over the last three decades. Domestic value-added in foreign exports as a share of gross exports in the Czech Republic is higher than the average share of the European Union 28. Services have a relatively low contribution to value-added in gross exports. Given the high integration of the Czech Republic into global value chains, it is crucial to take supply chain linkages into account when assessing the impact of trade shocks. The exposure to Germany is even more pronounced at the sectoral level. Manufacturing of machinery and transportation vehicles account for a large share of exports and imports in the Czech Republic. Although the impact of the US-China trade disputes on the Czech Republic would likely be limited, a hard Brexit scenario or lower demand in Germany could have sizable effects.